Teaching strategies for developing productive-divergent thinking among fast learners - Aquintey, Mary L. (College of Education, University of the Philippines Diliman, 1976)
The study is based on Williams' model for developing productive-divergent thinking. A lesson plan budget incorporated three class subjects, Social Studies, Science and Language (Dimension 1) using the classroom eaching strategies (Dimension 2) to bring about the seven productive-divergent thinking processes (Dimension 3). Thus, Williams' formula became the framework which the twenty six children enrolled in the Accelerated class were exposed to for a period of seven days.